2022
DOI: 10.3390/foods11060849
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality and Safety of the Spirulina Dietary Supplements Sold on the Slovenian Market

Abstract: The microalgae Spirulina may be a popular dietary supplement rich in essential nutrients and vitamins, but oversight of the supplement industry, in general, remains limited, and increasing incidents of adulteration, misbranding, and undeclared ingredients together with misleading claims create potential risks. In response, this study characterized the elemental, amino acid and fatty acid content of commercially available Spirulina supplements in Slovenia using EDXRF, ICP-MS and GC-MS and compared the results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 60 publications
1
20
0
1
Order By: Relevance
“…The concentrations of the elements in the samples vary depending on the producers. The obtained values for all five analyzed elements are in the concentration range of other Spirulina products described in the literature (3,(18)(19)(20)(21). Тhe following trend is observed: Mg > Fe > Mn > Zn > Cu.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The concentrations of the elements in the samples vary depending on the producers. The obtained values for all five analyzed elements are in the concentration range of other Spirulina products described in the literature (3,(18)(19)(20)(21). Тhe following trend is observed: Mg > Fe > Mn > Zn > Cu.…”
Section: Resultsmentioning
confidence: 62%
“…Based on the cylindrical arrangement of the multicellular trichomes, there are two types of filamentous cyanobacteria: Arthrospira (Spirulina) maxima and (Spirulina) platensis (2). Their main photosynthetic pigment is phycocyanin, which is blue in color (3), they also contain chlorophyll a, carotenoids and various pigments that can give them a red or pink color (4). Arthrospira (Spirulina) platensis is a natural inhabitant of tropical lakes with alkaline waters (pH>11), these conditions restrict the growth of other microorganisms but allow its cultivation (5).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae are usually considered as a valuable protein source as many species possess protein upto 70% dry weight and are nutritionally similar to proteins like egg and soybean (Amorim et al 2020 ) due to better digestibility and occurrence of essential amino acids. Species of Spirulina and Chlorella have approximately 60–70% protein (DW basis) with a good balance of essential amino acids required for human nutrition (Bleakley and Hayes 2017 ; Masten Rutar et al 2022 ). The free amino acid profile of Arthrospira sp., Haematococcus pluvialis, Acutodesmus acuminatus, Skeletonema costatum, and Botryococcus braunii w ere examined using reverse phase HPLC and it was found that Arthrospira sp.…”
Section: Microalgal Bioactive Compounds and Their Potential Biologica...mentioning
confidence: 99%
“…Results revealed that Spirulina is considered a healthy option by most of the participants. Rutar et al 10) showed that Spirulina-based food supplements would be reasonable when people choose a high protein, fatty acid, and amino acid content. Moreover, the statement "Spirulina absorbs CO2 for their growth and environment friendly" is positively scored by the consumers, approximately 91% for all responses.…”
Section: Willingness To Accept and Willingness To Paymentioning
confidence: 99%
“…Blue-green algae, Spirulina is a reasonably feasible resource of the high content of proteins (approximately 80%), vitamins, essential amino acids, minerals, and several high-value products 9,10) . Spirulina-based products are promoted and used in several countries, such as Japan, Germany, the USA, Italy, France, Canada, Chile, Mexico, Thailand, India, and so on 11) .…”
Section: Introductionmentioning
confidence: 99%